Effect of Mobile Instructional App on Students’ Performance in Christian Religious Studies - OJO, Oludare David; JAMBELANG, Abraham Ray (International Journal of Educational Management, 2025)
Gender differences is becoming critical within the context of teaching and learning education and Nigerian society. Thus, this study examined effect of mobile instruction app on students’ performance in Christian Religious Studies from the dimension gender. The research desigi adopted for this study was a quasi-experimental design T population of the study is 875CRS students in the department of Arts Educatic University of llorin. An intact class of 34 (1I males and 23 females) three hundred le undergraduates of Christian Religious Studies was purposively sampled for the st«c Two instruments were developed and used for this study: Mobile Instructional 1y (MIA) and Christian Religious Studies Performance Test(CRSPT) Descriptive statis ti ( mean) was used to answer the research question, the only null hypothesis of the stuc was tested using independent samples t-test. Findings revealed that there was 1 significant difference between male and female undergraduate students’ acadenn performance in the use of mobile instructional app in Christian Religious Studies. It vw recommended that university curriculum should be made flexible to accommodate th use of mobile devices for learning process, and that undergraduates should endeavou to explore the opportunities offered by mobile instructional app for an improve academic performance irrespective of gender difference.